FEATURES OF IGNEZING IN ADSORPTION OXIDATION AT LOSS OF WEIGHT - Zhai, Rupeng; Jia, Hailin (IJRDO-Journal of Applied Science, 2018)
In order to study the specific weightlessness stage and weightlessness characteristic point of adiabatic oxidation of coal gangue, the influence of oxygen concentration and heating rate on the adiabatic oxidation process of coal gangue under different operating conditions was studied by a comprehensive thermal analyzer. The experimental results show that the process of adiabatic oxidation weight loss of coal gangue under different conditions can be divided into four stages, that is, external water loss and water loss stage, internal water loss and water loss stage, volatilization combustion weight loss stage and fixed carbon combustion weight loss stage. With the same oxygen concentration (20%), the TG curve of adiabatic oxidation of coal gangue shifted to high temperature with the increase of heating rate. The four characteristic temperature points (start point, midpoint, inflection point and end point) The linear increase of the rate of increase and the maximum combustion rate of the volatile and fixed carbon combustion weightlessness phase tends to increase, but the quality of the various stages of change is basically the same. Under the same heating rate (10 ℃ / min), with the increase of oxygen concentration, the TG curve of adiabatic oxidation of coal gangue shifted to the low temperature region, and the characteristic temperature point (starting point, Midpoint, inflection point and end point) and weightlessness were basically not affected by the increase of oxygen concentration. The characteristic temperature points (start point, midpoint, inflection point and end point) of volatiles and carbon loss during stationary phase decreased with the increase of oxygen concentration .